2015
DOI: 10.1007/978-1-4939-2874-3_4
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Carbohydrate Recognition from Docked Ensembles Using the AutoMap Procedure

Abstract: Carbohydrate-protein recognition is vital to many processes in health and disease. In particular, elucidation of the structural basis of carbohydrate binding is important to the development of oligosaccharides and oligosaccharide mimetics as vaccines for infectious diseases and cancer. Computational structural techniques are valuable for the study of carbohydrate-protein recognition due to the challenges associated with experimental determination of carbohydrate-protein complexes. AutoMap is a computer program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…We have demonstrated that, as the result of all the above-mentioned challenges, docking programs and scoring functions are not always able to predict the native binding pose faithfully as the top docked pose. To overcome this shortcoming and to harness the recognition information embedded in the docking output, we have developed a site mapping methodology that takes into account an ensemble of docked poses and identifies binding site residues critically involved in recognition of a ligand or ligand family (Yuriev et al, 2001 , 2002 ; Agostino et al, 2013 ; Dingjan et al, 2015a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that, as the result of all the above-mentioned challenges, docking programs and scoring functions are not always able to predict the native binding pose faithfully as the top docked pose. To overcome this shortcoming and to harness the recognition information embedded in the docking output, we have developed a site mapping methodology that takes into account an ensemble of docked poses and identifies binding site residues critically involved in recognition of a ligand or ligand family (Yuriev et al, 2001 , 2002 ; Agostino et al, 2013 ; Dingjan et al, 2015a ).…”
Section: Discussionmentioning
confidence: 99%
“…All BambL-blood group carbohydrate complexes were examined using LigPlot (Wallace et al, 1995 ; Laskowski and Swindells, 2011 ). Only poses that passed the glycosidic torsion filter requirements (see above), were used for site mapping, following a previously developed method (Yuriev et al, 2001 ; Agostino et al, 2009b , 2011 , 2013 ; Dingjan et al, 2015a ). In brief, each individual hydrogen bond made by a particular BambL residue was counted toward the hydrogen-bond tally.…”
Section: Methodsmentioning
confidence: 99%